Пухлинні маркери: роль у клінічній практиці - Щербіна, О.В. (Iнститут експериментальної патології, онкології і радіобіології ім. Р. Є. Кавецького, 2008)
The purpose of the lecture is analysis of possibilities of tumor markers include screening, differential diagnosis of malignant and benign tumors, control of treatment efficacy, recognition of recidives and metastases. Described the role of tumor markers in patients with breast cancer.